Biological properties of European bitterling Rhodeus amarus (Bloch, 1782) in Dinsiz Stream, Turkey - Benzer, Semra; Gül, Ali (Universitas Malikussaleh, 2020)
The aim of this article was to some morphometric characteristics of Rhodeus amarus from Dinsiz Stream. A morphological analysis of 21 morphometric characters were done. These characteristics total length (TL); fork length (FL); standard length (SL); predorsal length; dorsal fin base length; dorsal fin length; head length; pretorbital length; eye diameter; postorbital length; interorbital distance; body height; preanal distance; anal fin base length; anal fin length; pectoral fin base length; pectoral fin length; ventral fin base length; ventral fin length; caudal peduncle depth and weight (W). The samples were measured weight to the nearest 0.01 g and total, fork and standard length to the nearest 0.01 mm. The total length (TL) and weight (W min-max) of the fish were 4.2- 7.1 cm and 1.699- 7.444 g, respectively.Keywords: Rhodeus amarus; European bitterling; morphometric properties; Dinsiz Stream Turkey